Analysis of Exopolysaccharides in Lactobacillus casei group Probiotics from Human Breast Milk - Nur Kusmiyati; Yuni Puspitasari; Ulfah Utami; Anggeria Oktavisa Denta (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2023)
Exopolysaccharides get a lot of attention because they can improve the host immune system. Exopolysaccharide is a polysaccharide that is produced and secreted from microbes outside the cell, usually found on the outside of the bacterial structure. The Lactobacillus casei group from human breast milk is thought to have the ability to produce exopolysaccharides. The purpose of the study was to examine the exopolysaccharide of the L. casei group that was isolated from breast milk. The methods used include the gravimetric, the phenol-sulfuric acid and the Fourier Transform Infra-Red (FTIR). The results showed that the L. casei group could produce exopolysaccharides, and had high exopolysaccharide total sugar content. Lactobacillus paracasei had the highest exopolysaccharide and total sugar content of 3660 mg/L and 80.6%, respectively. The FTIR results of the L. casei group exopolysaccharides showed the presence of hydroxyl functional groups O-H (3425.76-3295.98 cm-1), methyl C-H (2930.86-2856.70 cm-1), carbonyl C=O (1660.11-1647.27 cm-1), C-H (1456.16-1373.44 cm-1) and C-O-C ether (1071.08-1056.82 cm-1) which are specific characters of exopolysaccharides. Since the FTIR profile demonstrates that the L. casei group can produce exopolysaccharides, it has greater potential as a a probiotic.